Randomised control trial on the effects of letrozole and clomiphene citrate for induction of ovulation in polycystic ovarian syndrome (pcos). - Ismail, Munawwirah (2011)
Objectives: To compare the effectiveness of Letrozole and Clomiphene Citrate as ovulation induction agent in Polycystic Ovarian Syndrome (PCOS) in infertility. Methodology: Women who was diagnosed to have Polycystic Ovarian Syndrome (according to the revised Rotterdam ESHRE/ASRM criteria, (2004) attending Infertility Clinic at Hospital Sultanah Bahiyah, Alor Star, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan and Hospital Tengku Ampuan Afzan, Kuantan, Pahang were recruited in this study. They were later randomized by using computer generated to undergo on cycle of Letrozole ( n=75) or Clomiphene Citrate (n=75) induction. During initial visit, the Body Mass Index was measured and baseline investigations were taken which include Follicular Stimulating Hormone, Luteinising Hormone, Liver Function Test, Renal Function Test and serum prolactin. In Letrozole Group, Letrozole 5.0 mg daily was given from the fifth until the ninth day of menstruation. Clomiphene citrate 100 mg daily was given for those patients in CC Group from the fifth until the ninth day of menstruation as well. Serial tranvaginal scan were done at D2-D5 as a baseline then D10 of menses till to see the dominant follicles, endometrial thickness and number of follicles. Tranvaginal scan were repeated to look for evidence of ovulation. Result Total of 150 subjects enrolled in this study, completed the ovulation induction cycle and included in data analysis. There were no statistical differences noted in term of sociodemographic, anthropometrics and duration of infertility in between these two study groups suggestive that the subjects were homogenously distributed. The difference between letrozole and CC in term of ovulation rate, 59 (78.7%) vs 40 (53.3%); p <0.001 which was statistically significant, and pregnancy rate, 19 (32.0%) versus 12 (30.0%); p 0.817 which was statistically not significant. Letrozole also produce better dominant follicle which is monofollicle compare to CC, 33 (46.5%) versus 20 (26.7%) patients respectively. Endometrial response also yielded similar result with p value not significant. No incidence of adverse pregnancy outcome like Ovarian Hyperstimulating Syndrome (OHSS) observing in this study. Multiple logistic regression (MLR) shows letrozole group had three times more likely having ovulation outcome compare to CC group after controlling other variables of age, duration of infertility, type of infertility, baseline hormonal profile and BMI. Only BMI made significant contribution to predict successful ovulation. If BMI of a patient reduces by 1 unit kg/m2, there is a nine percent of chance of her to have successful ovulation. Conclusion Letrozole provide a more efficient stimulation to CC in term of ovulation induction and thicken the endometrial thickness even though the pregnancy rate was not significant among PCOS women undergoing ovulation induction.